Exploring Students’ Cooperative Learning Combined with Silent WayTeaching Approach As Part of Learner-centered Methodology Using Communication Practice in Enabling the First-Year Degree Students at an IT university to acquire English Fundamental Grammar Knowledge - Rumondang Miranda Marsaulina (Universitas Negeri Padang, 2014)
This study explored the results of the silent way teaching approach based on a structural syllabus with students’ cooperative learning strategy by communication practice as part of the use of learner-centered methodology in teaching fundamental English grammar to the first-year degree students in the second semester at an IT university. It also aimed to observe how students’ cooperative learning strategy accompanied with inquiry-based tasks have resulted in students’ grammar ability and what caused such outcome. This study was conducted through observing, informal talking to students to identify their problems and analyzing the students’ test results. The data examined was the grammar test scores of all first-year students at the university. The test was an isolated grammar problems measuring only what had been inquired and taught. The data were analyzed by tabulating the students’ test scores, counting the percentage of students who scored at, above or below the university’s standardized scale score and the percentage of the students who got high subscore level for the test questions exactly like those taught using the direct instruction and drilling pattern during the class. Based on the students’ low score level, it has been concluded the use of silent way teaching approach in the learner-centered methodology emphasizing students’ orally communicating what they had inquired resulted in their weakness of using the grammar itself even in an isolated way. The weakness relied on their little motivation to self-drilling themselves using the grammar on related worksheets throughout their process of cooperative learning.